ANALISIS DAN PERANCANGAN ARSITEKTUR ENTERPRISE STMIK PRIMAKARA - I Nyoman Yudi Anggara Wijaya; I Gusti Agung Ngurah Indra Adnyana (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTInformation strategic planning and information technology (SI / IT) are identified as key factors in IT integration and business alignment in organizations. Strategic planning carried out at Primakara STMIK uses the TOGAF framework to produce an enterprise architecture that will be a guideline for the development of information systems and information technology (SI / IT) that is aligned with Primakara's STMIK vision, mission and goals. The environmental analysis is done first, the environmental analysis uses SWOT analysis to get an overview of the strategic plan. Stages to get an overview of enterprise architecture and information system development roadmap include Architecture Vision, Business Architecture, Information System Architecture, which consists of: Data Architecture, and Application Architecture.Keyword :TOGAF, Enterprises Architecture, CollegeABSTRAKPerencanaan strategis informasi dan teknologi informasi (SI/TI) diidentifikasi sebagai faktor kunci dalam integrasi TI dan keselarasan bisnis pada organisasi. Perencanaan strategis yang dilakukan pada STMIK Primakara menggunakan kerangka kerja TOGAF untuk menghasilkan enterprise architecture yang akan menjadi pedoman untuk pengembangan sistem informasi dan teknologi informasi (SI/TI) yang selaras dengan visi, misi dan tujuan STMIK Primakara. Analisis lingkungan dilakukan terlebih dahulu, analisis lingkungan menggunakan SWOT analisis untuk mendapat gambaran rencana strategis. Tahapan untuk mendapatkan gambaran enterprises architecture dan roadmap pengembangan sistem informasi meliputi Architecture Vision, Business Architecture, Information System Architecture, yang terdiri dari: Data Architecture, dan Application Architecture.Kata Kunci : TOGAF, Perancangan Arsitektur Enterprise, Sekolah Tinggi.